Auditoría a los estados financieros del almacén el baratón, cantón Vinces, período 2013 - Arana Carriel, Melva Azucena (2015)
This research was carried out in the El Baraton warehouse located on the streets Bolivar and Sucre from the city of Vinces, Los Ríos, being the sale of appliances, its main commercial activity in its various lines as well as household items. During the first stage of this work was evaluated the internal control through the application of interviews, questionnaires and SWOT analysis. At the stage of implementation was verified the Balance sheet as well as the status of results for the period 2013, being responsible for the emission of the same administration. Applied techniques and audit procedures: observation, interviews, verifications, and calculations, which allowed us to obtain evidence of situations or reportable conditions in terms of the accuracy and fairness of the financial statements that we could have found. The scarcity of documents that you support compliance with internal controls established on an informal basis that makes activities susceptible to errors or irregularities. After the evaluation of the internal control was obtained a grade of a confidence level moderate as well as the risk of control as well as the risk inherent analyzed through the SWOT analysis technique; while the risk of audit was 0.76% considered acceptable. In terms of the findings, it may be mentioned that during the arc of box and take physical inventories and bank reconciliation differences between the physical and the books, in response to which is not adequate accounting control and the system that keeps the store is not sufficient for the needs of the company.